A Failure Mode Effect and Criticality Analysis of Conventional Milling Machine Using Fuzzy Logic: Case Study of RCM. (17th May 2016) - Gupta, G.; Mishra, R. P.
Abstract : The purpose of this paper is to select the appropriate maintenance strategies for each failure mode of functionally significant item of conventional milling machine. In order to describe the criticality analysis of conventional milling machine, this paper presents a study on reliability‐centered maintenance with fuzzy logic and its comparison with conventional method. On the basis of fuzzy logic, failure mode and effect analysis is introduced integrating with fuzzy linguistic scale method. After that, weighted Euclidean distance formula and centroid defuzzification is used for calculating risk priority number. The results indicate that based on risk priority number, value criticality ranking was decided, and appropriate maintenance strategies were suggested for each failure mode. It also reflects that a more accurate ranking can be performed by the application of fuzzy logic using linguistic rule to failure mode and effect analysis. Copyright © 2016 John Wiley & Sons, Ltd.